If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23y + -87 = y + -1(-82) Reorder the terms: -87 + -23y = y + -1(-82) Multiply -1 * -82 -87 + -23y = y + 82 Reorder the terms: -87 + -23y = 82 + y Solving -87 + -23y = 82 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -87 + -23y + -1y = 82 + y + -1y Combine like terms: -23y + -1y = -24y -87 + -24y = 82 + y + -1y Combine like terms: y + -1y = 0 -87 + -24y = 82 + 0 -87 + -24y = 82 Add '87' to each side of the equation. -87 + 87 + -24y = 82 + 87 Combine like terms: -87 + 87 = 0 0 + -24y = 82 + 87 -24y = 82 + 87 Combine like terms: 82 + 87 = 169 -24y = 169 Divide each side by '-24'. y = -7.041666667 Simplifying y = -7.041666667
| 0.5e+3=4+e | | 7m+9=5(m+3) | | 0.3x-1=0.5(x+2)-0.2x | | -3(1.8x-10.8)+12x=-2 | | x^2+16x+64=6 | | X=70/0.35 | | 12-20.5= | | 0.25(16-12c)=31 | | 12x+17=-12x-17 | | y+2/3=5/6 | | -3t-12+6t=5t-1 | | 6b-1=3b+8 | | 106=2(3+x)+2(x) | | -23x-87=x+82 | | -17.9-4.2= | | 8a-5=1 | | 4y^2-16-48=0 | | 8x+1=8x+16 | | b-7=5b+11 | | 3/2y=-6 | | 3x-2=4x-2 | | -2y-8=7y+10 | | 1/4b=39 | | g^2+17g+72=0 | | x^2/4-15+8 | | 11z-24=6z+1 | | 2x-5y=84x+7 | | 6(3t+2)=6 | | -6x-12-26=-14 | | 4x-4=10x-7 | | 15/135=22/x | | (z^2-5z)=0 |